Properties of geothermal fluids in Switzerland: A new interactive database - Sonney, Romain; Vuataz, François (My University, 2008)
A database on geothermal fluids in Switzerland, called BDFGeotherm, has been compiled. It consists of nine related tables with fields describing the geographical, geological, hydrogeological and geothermal conditions of each sampling location. In all, 203 springs and boreholes from 82 geothermal sites in Switzerland and neighboring regions are listed in this new interactive Microsoft Access database. BDFGeotherm is a functional tool for various phases of a geothermal project such as exploration, production or fluid re-injection. Many types of queries can be run, using any fields from the database, and the results can be put into tables and printed or exported and saved in other files. In addition to describing the database structure, this paper also gives a summary of the reservoir formations, the geographical distribution of hydraulic parameters, the geochemical types of thermal waters and the potential geothermal resources associated with the sites.
Keywords: Geothermal potential; Switzerland; Geothermal fluids; Geochemistry; Thermal springs; Deep boreholes; Database; MS Access; BDFGeotherm